PENINGKATAN LITERASI DIGITAL GURU MELALUI PKM WORKSHOP PEMBUATAN MEDIA INTERAKTIF BERBASIS ANDROID DI YAYASAN PONDOK PESANTREN NURUL HUDA OKU TIMUR - Arini Rosa Sinensis; Thoha Firdaus; Uli Riski (Jurnal Abdi Insani, 2023)
Technological developments in education lead teachers to continue learning with the aim of creating a more interactive and interesting learning experience for students. This is also in line with the implementation of the independent curriculum. Teachers at the Nurul Huda Islamic Boarding School Foundation are 56.3% of the total 253 teachers, teachers have not been able to utilize technology in learning and many of the teachers stated that they could not create technology-based interactive learning media such as making Android media. The aim of this Workhsop is to provide information and insight to teachers in using technology as a learning medium and provide training and practice in creating Android-based interactive media using Kodular applications. The methods for implementing this workshop are: 1) Providing material on digital learning innovations such as Artificial Intelligence and Kodular, 2) Training in Creating Android-Based Interactive Media with Kodular Applications, 3) Discussion and Problem Solving, 4) Assignments and Exercises, 5) Evaluation of Implementation Program. The results of this PKM workshop activity showed that YPPNH teachers had: 1) understood and added insight into technological developments in learning innovation, 2) knew how to create Android-based interactive media using the Kodular application and 3) had produced Android-based interactive media. with material according to the field of competency and subjects taught and, 4) the results of the implementation evaluation are seen from partner satisfaction with the implementation of the PKM Workshop on Making Android-Based Interactive Learning Media. The results of the questionnaire analysis showed that partners expressed satisfaction with an average percentage of 85.09% with the implementation of the Program or workshop activities. In conclusion, there has been an increase in teachers' digital literacy and their skills in creating Android media that can be used for classroom learning.